2020
DOI: 10.1002/pc.25774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stack sequence on the mechanical characteristics of hybrid composites analyzed using cone beam computed tomography and scanning electron microscopy

Abstract: The hybridization of composites has recently seen an exponential growth in acceptance due to its ability to improve the property such as toughness of composites. Hybridization of fibers is known to give a better balance of properties and increases the opportunity to use natural fibers, thereby reducing the impact on the environment without compromising utility. This study deals with hybridization of ultrahigh-molecular-weight polyethylene (UHMWPE) with natural fibers such as flax and jute using phenol formalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Most studies neglect using non-hybrid composites (only with synthetic or natural fiber) in their analyzes, limiting an effective improvement analysis of impregnation and the failure mechanisms (22)(23)(24). The most used type of hybrid is interleaved stacking sequence, as this increases the number of hybrid interfaces in the material, which with a positive synergy could significantly increase the mechanical performance (25). Two types of stacking called are also presented.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Most studies neglect using non-hybrid composites (only with synthetic or natural fiber) in their analyzes, limiting an effective improvement analysis of impregnation and the failure mechanisms (22)(23)(24). The most used type of hybrid is interleaved stacking sequence, as this increases the number of hybrid interfaces in the material, which with a positive synergy could significantly increase the mechanical performance (25). Two types of stacking called are also presented.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…A study on internal structure of sisal/kenaf composite with bagasse ash (BGA) as a filler captures only a few filler agglomerations [ 9 ]. In addition, a study on influence of stack sequence of UHMWPE (P), flax (F) and jute (J) hybrid composite subjected to flexural loading was investigated [ 10 ]. Through computed tomography test, it showed that FF-J-PP-J-FF composite had extensive fiber breakage followed by delamination of the composite specimen, with some areas of the specimen being intact.…”
Section: Introductionmentioning
confidence: 99%